(untitled) (International journal of artificial intelligence, 2026)
The increasing consumption of lubricating oils in automotive and industrial sectors has led to a significant rise in the generation of used motor oils, which pose serious environmental and health risks if improperly managed. Used motor oils contain hazardous contaminants such as heavy metals, polycyclic aromatic hydrocar, oxidation products, and degraded additives that can pollute soil, water, and air. This study focuses on the improvement of cleaning and regeneration methods for used motor oils in order to reduce their negative impact on the environment and promote sustainable resource management. Modern purification techniques, including mechanical separation, adsorption, membrane filtration, chemical treatment, and combined physicochemical processes, are analyzed and compared in terms of efficiency, economic feasibility, and environmental safety. Special attention is given to innovative low-waste and energy-efficient technologies that allow the recovery of base oil components while minimizing secondary pollution. The results indicate that the integration of advanced filtration and adsorption methods significantly enhances oil quality and extends its service life, thereby reducing the volume of hazardous waste. The implementation of improved cleaning methods for used motor oils contributes to environmental protection, supports circular economy principles, and decreases dependence on virgin petroleum resources.